2020
DOI: 10.2478/jas-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Lotmaria Passim As Third Parasite Gastrointestinal Tract of Honey Bees Living in Tree Trunk

Abstract: AbstractHoney bees (Apis mellifera L.) inhabiting trees in forests are not managed by humans or treated for pathogens; therefore, many researchers and beekeepers believe that viral, bacterial, and parasitic diseases may lead to their decline. The aim of the study was to evaluate the prevalence of L. passim and Nosema spp. in feral colonies by real-time PCR. This study was performed on twenty-six sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…( 23 ) analysed 357 trypanosomatid-positive samples in bumblebees and their sequencing revealed only one sample positive for L. passim . In our earlier research we also found L. passim in bumblebees ( 8 ). This research proves that this protozoan is commonly found in the environment and indicates that phylogenetic analyses should be carried out to test the difference in the strength of its affinity for individual species.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…( 23 ) analysed 357 trypanosomatid-positive samples in bumblebees and their sequencing revealed only one sample positive for L. passim . In our earlier research we also found L. passim in bumblebees ( 8 ). This research proves that this protozoan is commonly found in the environment and indicates that phylogenetic analyses should be carried out to test the difference in the strength of its affinity for individual species.…”
Section: Discussionsupporting
confidence: 50%
“…They showed the presence of these honey bee pathogens in hive beetles collected from free-flying colonies. Lotmaria passim colonise the guts of various insects like honey bees, bumblebees, solitary bees and wasps ( 8 , 10 , 15 ), to varying extents: Tripodi et al . ( 23 ) analysed 357 trypanosomatid-positive samples in bumblebees and their sequencing revealed only one sample positive for L. passim .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it led to a reduction in immune gene expression [37]. The high incidence of trypanosomatids is similar in other European countries [36,62].…”
Section: Discussionmentioning
confidence: 77%
“…Of even more concern is that trypanosomatids affect the composition of the symbiotic bacterial taxa of bees [40]. However, little is known about the full extent of the harmfulness and mechanism of pathogenesis of these two pathogens [38,62]. Other studies have shown an even higher risk of trypanosomatids when co-infected with N. ceranae [35][36][37].…”
Section: Discussionmentioning
confidence: 99%